Determination of the optimum date for planting cocoa hybrids in the Divo region (Côte d’Ivoire) - Assi, Evelyne, Marise (My University, 2022)
The cocoa tree, a crop highly prized in the world for its beans, is one of pillars of the Ivorian economy. However, it is confronted with numerous constraints including climatic disturbances which disturb the cropping calendar. The aim of this work is to determine an optimal planting date allowing a good establishment in the cocoa field. Thus, six-month-old plants were planted on different dates, in particular in March, April, May and June 2015. The parameters studied were the annual rainfall, the monthly distribution of the rains, the growing seasons of Divo, the mortality rate of the plants, the vegetative growth and the production. The results showed that cocoa trees planted in June expressed the highest survival rate (87.9%), followed by that of April (84.96%). The best increases in diameter and height were observed with the March and April plants. Regarding production parameters, the results showed that the March and April plants recorded the highest crowning rates with 66.3 and 57.8% respectively. The same was true of flowering where their rates were 35.4 and 30.3%. Production of cherries was higher in March (25.2%) and April (21.1%) plants. Ultimately the study shows that an early planting of cocoa trees is possible in the Divo region, at least, from the 3rd decade of March.
Keywords: Cocoa tree; Mortality; Planting date; Production; Rainfall